Disruption of the thyroid system by diethylstilbestrol and ioxynil in the sea bream (Sparus aurata) - Morgado, Isabel (2014)
Some environmental contaminants are thought to cause disruption of the thyroid system in vertebrates acting as endocrine disrupting chemicals (EDCs). Such chemicals may affect synthesis, transport and metabolism of thyroid hormones (THs). Ioxynil (IOX) and diethylstilbestrol (DES) are potential EDCs with strong affinity in vitro for sea bream transthyretin (TTR), a TH distributor protein (THDP). The aim of the present study was to establish how such chemicals influence the thyroid axis in sea bream (Sparus aurata). DES, IOX and propilthyouracil (PTU, a goitrogen) were administered in the diet to sea bream juveniles at 1 mg/kg fish (n = 14/treatment) for 21 days. After exposure plasma TH levels, quantified by RIA, were similar to those of control fish (p > 0.05) in all treatment groups. Analysis by quantitative PCR revealed that all treatments down-regulated TSH gene transcription (p < 0.05) in the brain and pituitary and deiodinase II and III transcription in the brain (p < 0.001). In contrast, PTU caused DII up-regulation in the liver (p < 0.05). Thyroid receptor beta (TR ) transcription was down-regulated in the pituitary by PTU (p < 0.001) and DES (p < 0.05). TTR plasma levels, quantified by ELISA, were elevated by all the chemicals including PTU (p < 0.001) which also increased TTR gene transcription in the liver (p < 0.05). Thyroid histology indicated follicular hyperstimulation in all treatments with marked hyperplasia, hypertrophy and colloid depletion in the PTU group. It appears therefore, that in vitro TTR-binders, IOX and DES, can strongly influence several components of the fish thyroid system in vivo but that the thyroid axis may have the ability to maintain or re-establish plasma TH homeostasis.